Nature's fury cyclone [videorecording] - Koenig, Teresita; Noxon, Nicolas; Wells, Richard J.; Williamson, Gail.; National Geographic Society, Washington, D.C. (Washington, D.C. The Society, 1995)
Chronicles some of the world's most shocking storms, including tornadoes, hurricanes, water spouts and other weather systems. From twisters sweeping across the Midwest's "Tornado Alley," to the vicious force of Florida's hurricane Andrew, to the deadly powerful typhoons of the Pacific, the forces of nature are among the most powerful forces on earth.
VHS.
Narrated by Peter Coyote ; edited by Emmanuel Mainesse.
Keywords: Tornadoes -- 1991. -- Kansas; Cyclone -- India -- Bangladesh; Floods; Hurricane -- 1991. -- Florida; Natural disasters; Geography